(untitled) (Journal of Nobel Medical College, 2018)
Background: Pancreatitis is well known for its painful state of illness causing a severe impact on the quality of life which can be followed by life-threatening long-term sequelae of diabetes mellitus and pancreatic cancer as its complications.The present study was conducted to evaluate biochemical findings and outcomes following treatment of ICU admitted patients suffering from pancreatitis in Nobel Medical College Teaching Hospital (NMCTH). Materials and Methods: All the patients admitted in the ICU of NMCTH from 15th January 2017 to 14th January 2018 having been diagnosed as suffering from pancreatitis were enrolled in this study. Age, sex, differential diagnosis, blood amylase and lipase level and outcomes of the treatment of the patients were measured as major variables. Blood amylase and lipase level of these patients were estimated in the department of Biochemistry, NMCTH by the standard protocols using Randoxkits, provided by the manufacturer. The study was carried out after getting the approval from Institutional review committee (IRC). Statistical significance was compared using Student’s two-tailed t-test. Results were considered significant if p ≤ 0.05. Results: The number of patients admitted in ICU and suffering from pancreatitis was 136 out of 2204 total admission in ICU within a period of 1 year. Out of 136 pancreatitis patients, 44 were of biliary pancreatitis, 40 of alcoholic and 52 were patients of pancreatitis suffered from some other unknown factors. The mean age of the patients was 41.5±14.2 year. While analyzing the pancreatitis cases gender wise, it was found that male (N=80) were more sufferers than females (N=56). The mean ±SD value of blood amylase and lipase of these patients with pancreatitis were 1040±1062 IU/L & 442±425 IU/L respectively, which was significantly higher than the normal range. The maximum numbers of pancreatitis cases were seen in age group (30-39), (44 patients). It was found in our study that male patients were more sufferers of alcoholic pancreatitis than females; where as female patients were more in number among patients with biliary pancreatitis than males. The patients after getting the proper line of treatment, 88 of them recovered completely without any complication, 38 patients developed some complication, in which 26got recovered fully and 12 were referred. Mortality was seen in 10 patients. Conclusion: The results shows a very high prevalence rate of pancreatitis, the highest number being shared by those suffering from unknown factors followed by biliary pancreatitis and alcoholic pancreatitis in the descending order. In biliary pancreatitis, female patients are more whereas, the males are taking the major share among alcoholic pancreatitis. The level of the marker enzymes (amylase & lipase) are significantly higher than the normal confirming the cases to be of pancreatitis. Out of 136 patients, except for 12 cases referred and 10 patients died, all are fully recovered and discharged.